A Conceptual Framework on Play Learning: Rediscover Children Play Space in Kuala Lumpur High Rise Public Housing to Cultivate Play Learning - Lu , Chiao Er; Sharif, Roslina (MAJ - Malaysia Architectural Journal, 2023)
Neighborhood area plays an important role in children's play learning but children’s ability to go outdoor and experience the natural environment is under threat due to the fear and risk, lack of investment environment, overcrowding, and poverty. Previous studies highlighted low-cost housing residents' major dissatisfaction towards their community life. However, previous studies have only mentioned the dissatisfaction of adult residents and children who live in low-cost housing space quality are also important as it will affect children growth development especially children who need space to cultivate play learning. Play opportunities and environments that promote play, exploration and hands-on learning are at the core of effective learning program. Therefore, this research will rediscover children play spaces in Kuala Lumpur high-rise public housing to cultivate play learning. In this research, interviews will be used as the research inquiry and will conduct interviews on children's preference of space and the characteristic of space that encourage play learning. This research will discover spaces to cultivate play learning for children in Kuala Lumpur public housing. This research will contribute to the Ministry of Housing and Local Government, Local Authority Council, and Kuala Lumpur City Hall. The benefits of this research will be improving existing public housing common spaces and improving design guidelines for the future public housing project. Future research can be researched using survey questionnaires towards bigger sampling. In conclusion, this study is to discovering potential space in existing Kuala Lumpur public housing to cultivate play learning for children.